2018
DOI: 10.1590/1981-6723.16317
|View full text |Cite
|
Sign up to set email alerts
|

Análises de açúcares e ácidos clorogênicos de cafés colhidos em diferentes estádios de maturação e após o processamento

Abstract: Resumo Componentes como açúcares e ácidos clorogênicos, que são acumulados durante a maturação dos grãos de café, possuem importante papel na qualidade da bebidanão somente atribuído a sua alta concentração, mas também às alterações ocorridas nos grãos durante a torração. Os açúcares predominantes nos grãos de café são frutose, glicose e sacarose. Porém, os ácidos clorogênicos podem ser responsáveis pela desvalorização na qualidade da bebida, devido à intensa degradação térmica durante o processamento dos grã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…It was observed that the levels of fructose, glycerol, and glucose significantly decreased after drying, while the sucrose content increased, corroborating the results of Santos et al [ 51 ]. The reduction in reducing sugars, like glucose and fructose, may be attributed to fermentative processes occurring during the drying period [ 52 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It was observed that the levels of fructose, glycerol, and glucose significantly decreased after drying, while the sucrose content increased, corroborating the results of Santos et al [ 51 ]. The reduction in reducing sugars, like glucose and fructose, may be attributed to fermentative processes occurring during the drying period [ 52 ].…”
Section: Resultssupporting
confidence: 88%
“…Higher concentrations of sugars in raw beans can lead to an increase in these components during the roasting process, and there is a crucial relationship between the quantities of nonreducing and reducing sugars and coffee quality. However, there is no consensus in the literature regarding the type and concentration of sugars in beans that influence the quality attributes of the beverage, such as aroma, taste, acidity, bitterness, and color [51]. Different letters indicate statistically significant differences between the coffee samples (p ≤ 0.05).…”
Section: Sugars and Glycerolmentioning
confidence: 99%
“…The values found showed no statistically significant difference (p > 0.05). The rapid decrease of pH and the gradual increase of lactic acid indicate an increase of lactic acid bacterium and, thus these sugars (glucose and fructose) were available, then microorganisms metabolized them (Santos, Prado, Pertierra, & Palacios, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Em relação ao teor de Açúcares Redutores (AR), foi observado que as primeiras 24 h de infusão (amostras CB12 e CB24) não apresentaram diferença, entretanto, após 36 h (CB3) e 48 h (CB4) de infusão houve um aumento significativo nos valores de AR de 0,25 ± 0,00 e 0,28 ± 0,00 %, respectivamente (Tabela 2). De modo geral, os açúcares são fundamentais para a percepção sensorial, em especial, são conhecidos pela sensação "adocicada" ao degustar uma xícara de café (Santos et al, 2018).…”
Section: Pe (%)unclassified